Comparative Transcriptome Profiling Analysis Reveals the Adaptive Molecular Mechanism of Yellow-Green Leaf in Rosa beggeriana ‘Aurea’ - Gan, Ying; Kou, Yaping; Yan, Fei; Wang, Xiaofei; Wang, Hongqian; Song, Xiangshang; Zhang, Min; Zhao, Xin; Jia, Ruidong; Ge, Hong; Yang, Shuhua (Frontiers in Plant Science, 2022)
Rosa beggeriana ‘Aurea’ is a yellow-green leaf mutant and originated from Rosa beggeriana Schrenk by 60Co-γ irradiation, which is an important ornamental woody species. However, the molecular mechanism of the yellow-green leaf mutant remains unknown. Herein, comparative transcriptome profiling was performed between the yellow-green leaf (yl) type and normal green color type (WT) by RNA sequencing. Total of 3,372 significantly differently expressed genes (DEGs) were identified, consisting of 1,585 up-regulated genes and 1,787 down-regulated genes. Genes that taking part in metabolic of biological process (1090), membrane of cellular component (728), catalytic (1114) and binding of molecular function (840) were significant different in transcription level. DEGs involved in chlorophylls biosynthesis, carotenoids biosynthesis, cutin suberine and wax biosynthesis, as well as photosynthesis, chloroplast development, photosynthesis-antenna proteins, photosystem I and photosystem II components, CO2 fixation, ribosomal structure and biogenesis related genes were down-regulated. Meanwhile, linoleic acid metabolism, siroheme biosynthesis and carbon source of pigments biosynthesis through MEP pathways were up-regulated. Moreover, a total of 147 putative transcription factors were signification different expression, involving NAC, WRKY, bHLH, MYB and AP2/ERF, C2H2, GRAS, bZIP family gene. Our results showed that the disturbed pigments biosynthesis result in yellow-green leaf color by altering the ratio of chlorophylls and carotenoids in yl mutants. yl mutants may evoke other metabolic pathways to compensate for the photodamage caused by insufficient structure and function of chloroplasts, such as enhanced MEP pathways and linoleic acid metabolism to against oxidative stress. This research can provide a reference for application of leaf color mutants in the future.